2006
DOI: 10.1037/1528-3542.6.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety selectively disrupts visuospatial working memory.

Abstract: On the basis of a review of the extant literature describing emotion-cognition interactions, the authors propose 4 methodological desiderata for studying how task-irrelevant affect modulates cognition and present data from an experiment satisfying them. Consistent with accounts of the hemispheric asymmetries characterizing withdrawal-related negative affect and visuospatial working memory (WM) in prefrontal and parietal cortices, threat-induced anxiety selectively disrupted accuracy of spatial but not verbal W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
328
6
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 328 publications
(366 citation statements)
references
References 215 publications
(314 reference statements)
28
328
6
4
Order By: Relevance
“…Recent research also shows that negative affect can support memory of details, while positive affect increases working memory performance and supports memory of the "big picture" of situations [1,32]. Another experiment found that anxiety (which falls under negative affect) can significantly disrupt visuospatial working memory, leaving verbal working memory intact [45]. Our study is partially based on these prior findings, and apply the same text-based affective priming techniques as presented by Goeritz and Verheyen [21,48].…”
Section: Affect and Cognitionsupporting
confidence: 53%
“…Recent research also shows that negative affect can support memory of details, while positive affect increases working memory performance and supports memory of the "big picture" of situations [1,32]. Another experiment found that anxiety (which falls under negative affect) can significantly disrupt visuospatial working memory, leaving verbal working memory intact [45]. Our study is partially based on these prior findings, and apply the same text-based affective priming techniques as presented by Goeritz and Verheyen [21,48].…”
Section: Affect and Cognitionsupporting
confidence: 53%
“…In addition, in people with schizophrenia it has been found that increased physiological reactivity is associated with increased CD for negative topics (Docherty et al, 2001). One issue for future research might be to more directly examine whether in disorganized schizotypy there is an increased effect of emotion on cognition (Martin & Clore, 2001), or more specifically of emotion on working memory (e.g., Shackman et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, poorer performance on the Tower of Hanoi task in left-handed participants may reflect the higher levels of state anxiety displayed by left-handed people in novel situations (Wright, & Hardie, 2012) and the disruption of visuospatial working memory caused by anxiety (Shackman et al, 2006).Future research may further compare the performance of left and right-handed participants on novel tablet based tasks.…”
Section: Discussionmentioning
confidence: 99%